The impact of tobacco smoking and electronic cigarette vaping on salivary biomarkers. A comparative study - Naglaa M. Kamal; Noha S. Shams (Elsevier, 2022)
Objectives: This study aimed to investigate the effect of electronic cigarette vaping and cigarette smoking on the levels of interleukin-1β and transforming growth factor‑β salivary biomarkers compared to non-smokers. Methods: One hundred and fifty people participated in this study; There were 50 participants who smoked traditional cigarettes, 50 who used electronic cigarettes, and 50 healthy people who had never smoked cigarettes (control group). Furthermore, 5 ml of unstimulated whole saliva was sampled and clarified by centrifugation and frozen until analysis. Interleukin-1β and transforming growth factor‑β concentrations were assessed in saliva samples using ELISA. The duplicate readings average was utilized to interpret the data. Results: We found that cigarette smokers had significantly higher levels of interleukin-1β and transforming growth factor‑β than non-smokers and electronic cigarette users (p < 0.05). The difference between control participants and electronic cigarette users, as well as that between control participants and traditional cigarette smokers, was statistically significant (p < 0.05). Conclusion: Electronic cigarette users have higher levels of inflammatory and cancer risk biomarker than non-smokers, suggesting that electronic cigarettes can pose a risk of developing systemic diseases but less than conventional cigarettes. In conclusion, our study could be regarded as new evidence supporting the hazardous effects of e-cigs using a cost-effective, non-invasive method.